Obtenção e caracterização de películas biodegradáveis de amido de mandioca incorporados com celulose bacteriana - Cordeiro, Naiara de Freitas (2015)
One of the of the packaging industry challenges is the production of films using as raw material biopolymers that are at the same time biodegradable and derived from renewable source. In this context, starch stands out as a potential raw material because of its abundance and low cost. Starch films are brittle due to high intermolecular force, these films have low resistance to traction, making a low quality material, being not viable for the production of food packaging. The impregnation of bacterial cellulose can be a viable way to increase the tensile strength of biodegradable films. It was possible to evaluate mechanical properties and permeability. In this work were produced biodegradable films from cassava starch with bacterial cellulose incorporation. It was possible to evaluate mechanical and barrier properties. The addition of bacterial cellulose in two concentrations (1% and 5% in relation to starch) presented significant difference in the results of solubility, moisture, tensile strength, Young’s modulus and puncture test. The increase of bacterial cellulose amount at films formulation leaded to largest film tensile strength and Young’s modulus. There was a decrease films in solubility with bacterial cellulose addition . The incorporation of bacterial cellulose leaded to a rough surface morphology. In this way, the produced films can be applied in the field of packaging for the food industry, using them as a secondary food packaging.